AB0336 Clinical significance of serial measurement of anti-citrullinated protein antibodies (ACPA) in patients with palindromic rheumatism. (23rd January 2014) - Cabrera-Villalba, S.R.; Ruiz-Esquide, V.; Gomez-Puerta, J.A.; Hernandez, M.V.; Salvador, G.; Cañete, J.D.; Sanmarti, R.
Abstract : Background: Anti-citrullinated protein antibodies (ACPA), the most specific markers of rheumatoid arthritis (RA), are found in approximately 50% of patients with palindromic rheumatism (PR). A significant proportion of these patients may evolve to RA. Objectives: To analyze the clinical significance of serial measurements of ACPA in patients with PR as biomarkers of progression to RA. Methods: All patients diagnosed with PR (Guerne et al criteria 1 ), attended by our Arthritis Unit were included. We analyzed only patients considered as pure PR (without evidence of persistent arthritis or other chronic rheumatic disease at the first measurement of ACPA). ACPA were analyzed in serum by commercial tests; CCP1 (until 2002) and CCP2 (from 2003). Clinical data were collected during follow-up, establishing the date of diagnosis of RA (1987 ACR criteria) or other rheumatic diseases. Results: Seventy-one patients (54F/17M) with an initial diagnosis of pure PR and a mean follow up time of 7.6±4.7 years (range 1.1-17.7) were included after the first determination of ACPA. In 57 (43F/14M) patients, ≥2 serial measurements of ACPA were available. At the first ACPA measurement, 35 patients were ACPA positive and 22 ACPA negative. Fourteen patients (24.6%) evolved to RA after a mean of 8.5±5.1 years. ACPA positive patients more-frequently developed RA than ACPA negative patients (31.4% vs 13.6%, p 0.2). Thirty-eight patients (66.7%) remained with a diagnosis of PR and 8.8% evolved to another rheumatic disease. Forty patients (70.2%) were treated with antimalarials (chloroquine or hydroxychloroquine). The mean ACPA serum measurement was 3.3±1.5 (range 2-8) and in 64.9% of patients 2-3 determinations were made. The mean time from the first to the last measurement was 70.3±49.9 months. ACPA remained positive in successive measurements in all patients ACPA positive at baseline. ACPA levels remained stable during follow-up (mean of 744.9±598.4 IU at the first and 629.1±528.5 IU in the last measurement, p>0.05. Seroconversion occurred at 11 and 18 months of follow up, respectively, in two of the 22 patients ACPA negative at baseline, one of whom evolved to RA. Conclusions: ACPA are common in the sera of patients with PR and although ACPA positivity is a risk factor of progression to RA, a significant number of patients with positive ACPA do not evolve to RA or another chronic rheumatic disease during a long term follow-up. ACPA serum levels remained stable over time and seroconversion is uncommon after the onset of symptoms of RP. References: Guerne PA, Weissman MH, AM J Med.1992:93:451-60. Disclosure of Interest: None Declared